Do changes in the business environment and sustainable development really matter for enhancing enterprise development?. (15th September 2022) - Brychko, Maryna; Bilan, Yuriy; Lyeonov, Serhiy; Streimikiene, Dalia
Abstract: The accomplishment of sustainable development goals has become a global initiative to encourage renewable energy, reduce wasteful energy consumption and increase investment in energy efficiency projects. The number of publications devoted to sustainable development, environmental protection and green investments is growing exponentially. Firstly, this study is committed to provide a comprehensive overview of research literature on enterprise development in decades‐long, focusing on the sustainable development and business environment field. Secondly, it seeks to elaborate the most comprehensive structural model examining the multilateral and facilitative role of internal and external business environment changes in the relationship between sustainable development and enterprise development. A bibliometric analysis via VOSviewer was applied to detect and visualize the research trends and display the research status of enterprise development under the changes in the business environment and sustainable development. A confirmatory factor analysis and structural equation modeling were performed to develop, implement and verify a conceptual structural model examining the multilateral and facilitative role of internal and external business environment changes in the relationship between sustainable development and enterprise development. Mapping bibliographic data based on co‐citation, co‐occurrence, bibliographic coupling, and network and content analysis showed that generally, researchers had made significant efforts to investigate different links that arise between enterprises development, sustainable development, and business environment separately in different combinations. Structural equation modeling showed that the argument that sustainable development directly causes enterprise development is disputable since sustainable development focuses on changes in the internal and external business environment that eventually influence enterprise development, which in turn leads to a further new shift in the external environment.